Development of downsized bolter robot for lunar structures - Madestam, Jakob (My University, 2025)
This master’s thesis project in Product Development at Chalmers University of Technology presents the development of a downsized version of the MMIC-I robot, called mini MMIC-I (mMMIC-I), within NASA’s ARMADAS project. The project was conducted during the spring of 2025 at NASA Ames Research Center in San Francisco, California. ARMADAS focuses on autonomous assembly of large structures in space using modular building blocks (voxels). With the goal of raising the technology readiness level (TRL) of the ARMADAS system and preparing for a potential CubeSat mission, this work investigates the feasibility of scaling down the MMIC-I robot to operate within a 1.5 U voxel size (150 mm x 150 mm x 150 mm). The project followed an agile-inspired product development methodology, combining iterative prototyping, structured evaluation, and reflective learning processes. A two-week sprint structure guided the development timeline, enabling continual feedback and design refinement. The methodology included prototyping with increasing fidelity. Emphasis was placed on balancing fast prototyping cycles with sufficient analytical groundwork to avoid over-engineering within the project’s limited fourmonth duration. During the project, two iterations of mMMIC-I were prototyped and evaluated. While the latest prototype does not perform with the same reliability as MMIC-I, it can be concluded that through further iterations, a version that can perform reliably in 1.5 U voxels is possible. The project also discusses how different aspects of robotic simplification can be applied to the mMMIC-I design and what the required upcoming development steps before flight are.
Keywords: MMIC-I; ARMADAS; Robotics, Lunar; Down-Scaling; Redesign; Voxels; mMMIC-I; NASA; Design-simplification